COMPLEX OF PROGRAMS FOR SIMULATING MODELS OF TASKS OF RECONFIGURABLE COMPUTER SYSTEMS USING PRIORITY MASS SERVICE NETWORKS - Martyshkin, Alexey (Revista Inclusiones, 2019)
The paper provides refined mathematical models of task managers for reconfigurable and distributed computing systems. The developed models are based on queuing networks with FIFO and priority disciplines. The description of the created software package for the simulation of the specified classes of dispatchers as part of a reconfigurable system with the specified parameters is presented. The proposed software package has the ability to conduct simulation and obtain the characteristics of the entire reconfigurable system, as well as its individual nodes. The main difference between the developed software package and its analogues is the ability to simulate a queuing network which includes systems with a queue length limitation before the serving device and priority queuing systems, which allows a wider range of data of interest to obtain. The complex is easy to use and does not require knowledge of the modelling language. A set of programs can be used by developers of operating systems for their research and debugging at the development stage.